Marketing Improvement through Online Marketplace Usage Training for Micro-Business in Jati Village, Tuban - Amalia Anjani Arifiyanti; Nurjanti Takarini; Rohmatul Faizah; Anajeng Esri Edhi Mahanani (Future Science)
Internet access in Indonesia currently covers many parts of Indonesia. These developments are now progressing rapidly with the use of smartphones by the Indonesian people. With the ease of internet access and the high usage of electronic gadgets, they will supports in various activities carried out by the community. These kinds of activities included in buying and selling transactions. This online transaction is not restricted by region and time. The online transaction can be through an online marketplace. One of familiar online marketplace in Indonesia is Tokopedia. The communities in Jati Village, Soko, Tuban where the majority of the people owns micro businesses can sell their product through this platform. Selling through this platform has many advantages, such us this platform provide free service for seller and this platform has a high number of users in Indonesia. Because of that reason, the training Tokopedia seller for micro-business owner in Jati village was held. The result of this training expected that micro-business owner can sell their product through this platform. This will help them for marketing their products more easily and have wider customer coverage. In this training, as many as twenty four micro-business owners attended and participated in the training actively and enthusiastically.